Thermal, morphostructural and spectrometric characterization of an antibacterial kaolinite-based filter modified with silver for water treatment - Guizellini, Filipe Corrêa [UNESP]; Franzin, Bruno Trevizan [UNESP]; da Silva, Matheus Antonio [UNESP]; Abra, Luciana Mazotti [UNESP]; Hojo, Ossamu [UNESP]; Pastre, Iêda Aparecida [UNESP]; Ribeiro, Clóvis Augusto [UNESP]; Paiva-Santos, Carlos de Oliveira [UNESP]; Fertonani, Fernando Luis [UNESP] (Springer Nature, 2020)
The aim of this work is to synthesize and characterize a new structured silver–clay dried, calcined or sintered at different temperatures composite by TG–DTA analysis, FTIR spectrometry analysis, XRD and Rietveld refinement, WD-XRF spectrometry, FEG–SEM images and EDS chemical analysis and to evaluate the antibacterial capacity of the new composite by the diffusion disk test against E. coli strains to attend water potability parameters. TG–DTA curves of Bco_dried suggested the presence of kaolinite, muscovite and hydrotalcite by the different events of structural water loss at different atmospheres. The interaction of Ag–clay might have occurred with hydrotalcite as can be inferred by the disappearance of the event at 408.9 °C (N2) and 433.4 °C (air). FTIR spectra showed that the modification occurred because of the changes that can be observed in the band range of (750 ≤ ν ≤ 1350) cm−1 for inner –OH and Si–O bonds. The Bco_dried composition was quantified by XRD and Rietveld refinement, and crystalline phases are quartz, calcite, kaolinite, hydrotalcite, muscovite, and portlandite. After sintering, the material presented the formation of new crystalline phases, due to the loss of structural water. When modified, the sample had no characteristic peaks of hydrotalcite, suggesting an interaction with Ag species. The compositions estimated for all samples by WD-XRF are mostly of Si, Al, Ca, K, Mg, Fe, Ti, and Ag. After modification, Ag increased significantly for Pca4_dried and Pca4_sint. SEM images presented the hexagonal characteristic of layered clay material and showed the interaction with Ag added. The susceptibility test showed that Pca4_dried has an antibacterial capacity against E. coli JM107 strains.
Keywords: Antibacterial clay filter for water treatment; FEG–SEM images; FTIR; TG–DTA; WD-XRF; XRD